Vaginismus treatment with libido increase and practice - Yalcin Bahat, Pinar; Aslan Çetin, Berna; Turan, Gökçe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Vaginismus is an involuntary contraction of the vaginal muscles which makes sexual intercourse difficult or impossible. It is one of the more common female psychosexual problems. The cases illustrate that it is important to rule out the possibility of vaginismus among patients with infertility. The aim of the report was to share with readers the cases with common presentations and underlying psychological causes.